Molecular encapsulation of cinnamaldehyde in V-type starch: the role of solvent and temperature - Gao, Qing; Sun, Yanan; He, Ruolan; Zheng, Jiabao; Zhang, Bin; Tan, Chin Ping; Fu, Xiong; Huang, Qiang (Elsevier BV, 2023)
In this study, starch-cinnamaldehyde complexes were prepared by wet method (aqueous ethanol solvent) and dry method (solvent-free) under different temperatures to regulate the formation ability, release behavior, and antibacterial activities of starch-cinnamaldehyde complexes. Successful inclusion complexes (ICs) between V-type starch and cinnamaldehyde were detected only at the wet method preparation over 65 °C. Increasing the complexing temperature facilitated the formation and ordered structures of wet method-prepared starch-cinnamaldehyde ICs, but not for those prepared by dry method. The encapsulation efficiency of cinnamaldehyde in wet method ranged from 15.25 to 62.38 mg/g, significantly higher than that in dry method (12.39–17.20 mg/g). In wet method, ethanol concentration at 50 (w/w) could elevate the complexation efficiency compared with ethanol concentration at 40 and 60 (w/w). Notably, IC prepared using 50 (w/w) aqueous ethanol at 75 °C (75 °C 50 IC) contained the highest cinnamaldehyde content (62.38 mg/g) and largest degree of long- and short-range molecular order. Despite the high volatility of cinnamaldehyde, the 75 °C 50 IC sustainably released the cinnamaldehyde for over two weeks at 50 °C and 57 relative humidity, and it also exhibited significant inhibition against Staphylococcus aureus and Escherichia coli.